PERILAKU VERBAL DAN NONVERBAL DALAM RANAH KESEHATAN PADA MASYARAKAT DI DUSUN TAMBRAN KIDUL KECAMATAN SEMIN KABUPATEN GUNUNGKIDUL (KAJIAN ETNOLINGUISTIK) - Die Bhakti Wardoyo Putro; Inyo Yos Fernandez; Wakit Abdullah (Prasasti: Journal of Linguistics, 2016)
The aims of this study are (1) to describe the view of health and sickness in the cummunity of Tambran Kidul village; (2) to describe verbal and nonverbal behavior in healing and preventing the sickness in the cummunity of Tambran Kidul village; (3) to explain the reasons why verbal and nonverbal behaviors are very essential in healing and preventing the sickness on cummunity of Tambran Kidul village; and (4) to describe mindset, view of life, and worldview in the domain of health on the cummunity of Tambran Kidul village, Semin district, Gunungkidul regency.